1998
DOI: 10.1177/019262339802600114
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bladder Carcinogenesis

Abstract: Urinary bladder carcinogenesis in rodents bears numerous similarities to the diseases in humans. In rats, the process progresses through the morphologic stages of simple hyperplasia, papillary and nodular hyperplasia, papilloma, noninvasive, and invasive carcinoma. In mice, the pathogenesis can be similar or can follow a sequence of marked dysplasia with or without hyperplasia, leading to carcinoma in sirir and ultimately to high-grade invasive carcinoma. Although the papillary and nonpapillary diseases appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(77 citation statements)
references
References 34 publications
5
71
0
1
Order By: Relevance
“…Acrolein did not induce tumors in several studies in mice and rats and, when administered by inhalation to hamsters, did not enhance the carcinogenicity of either benzo [a]pyrene or N-nitrosodiethylamine (7). It did however produce bladder tumors in rats when given as a tumor initiator, followed by promotion with dietary uracil (18). The potential role of acrolein in cigarette smoke induced lung cancer requires further research.…”
Section: Discussionmentioning
confidence: 97%
“…Acrolein did not induce tumors in several studies in mice and rats and, when administered by inhalation to hamsters, did not enhance the carcinogenicity of either benzo [a]pyrene or N-nitrosodiethylamine (7). It did however produce bladder tumors in rats when given as a tumor initiator, followed by promotion with dietary uracil (18). The potential role of acrolein in cigarette smoke induced lung cancer requires further research.…”
Section: Discussionmentioning
confidence: 97%
“…PFOS is not likely to be insoluble in human urine (solubility, 305 µg/mL at 23-24°C) at the serum concentrations present in these workers (Ellefson 2001). In a review article, Cohen (1998) reported that all of the chemical agents listed as known bladder cancer agents were genotoxic and had metabolites that were genotoxic or precipitated in the urine. Given the consistency of the data analyzed, we hypothesize that the average serum PFOS concentrations in nonoccupational adult populations may range from 30 to 40 ppb, with 95% of a population's serum PFOS concentrations below 100 ppb.…”
Section: Article | Perfluorooctanesulfonate In Blood Donorsmentioning
confidence: 99%
“…22 Acrolein is mutagenic in bacterial and mammalian cells, 23,24 including human, 25,26 and is carcinogenic in rats. 27 Crotonaldehyde is genotoxic and mutagenic in human lymphoblasts 28 and induces liver tumors in rodents. 29 4-HNE induces a DNA damage response in Salmonella typhimurium ,30,31 but is inactive in bacterial mutagenesis assays.…”
Section: Introductionmentioning
confidence: 99%